Tree-ring growth and hydro-climatic variability in temperate dendrochronologies of northern mexico (2014)
This report addresses the following questions: a) is the diameter growth described by the standard ring width anomaly (SRWA) of Psudotsuga menziesii (Mirb.) Franco trees related to precipitation (P), pan evaporation (E), evapotranspiration (Et), runoff (Q), and soil moisture content (θ) derived from a water balance model?; b) is the SRWA associated with synoptic climate events such as El Nino Southern Oscillation (ENSO), the Pacific Decadal Oscillation (PDO), and the Atlantic Multidecadal Oscillation (AMO)?, and c) are P, Et and θ related to ENSO, PDO and AMO events? The SRWA for three dendrochronologies (Las Bayas and Banderas in Durango and El Gato in Zacatecas) from 1665 to 2001 addressed these questions. Instrumental measurements of P and E (1947-2007) and, using parameterized sub-models for the rainfall interception of Gash model (I) and Et, a mass balance approach evaluated Q and θ for a forest site near El Salto, Durango, Mexico. SRWA oscillations of several timescales had spectral peaks every 2-3; 3-7; and 9-12 years. The ENSO indices explained most of the total SRWA variation for all three chronologies (1990-2001). For the short (1990-2001) and middle-term (1945-2001) seasonal data, the SRWA variability was only linked to θ. The strength of the relationship weakened as the length of the time series increased, indicating that other variables control tree growth as well. The ENSO takes, on average, 4 to 8 months to display its effect on the hydrological variables and diameter growth in northern P. mensiezii trees of Mexico, making tree growth predictable.